2020
DOI: 10.1111/jfr3.12599
|View full text |Cite
|
Sign up to set email alerts
|

Bridge pier shape influence on wood accumulation: Outcomes from flume experiments and numerical modelling

Abstract: Streamwood accumulation at bridges exerts additional forces to bridge structures and may aggravate flooding, local scouring, and eventually may lead to bridge collapse. However, the important ecological role of streamwood in fluvial systems calls for a compromise between preservation of river ecosystems and prevention of streamwood‐related hazards (e.g., bridge clogging). This study evaluates the effect of bridge pier shape on wood accumulation or blockage, probability in lowland type of rivers. We conducted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Past experiments seemed to confirm preferential patterns for both straight channel (Bocchiola et al, 2008) and curved reach (Schmocker and Weitbrecht, 2013), but could not provide any evidence to confirm the theory by Diehl (1997). De Cicco et al (2020 observed in a flume experiment that LW elements released at the flume centerline occupied a narrow area of the flume center for F r=0.50, whilst for lower F r (i.e.…”
Section: Introductionmentioning
confidence: 70%
“…Past experiments seemed to confirm preferential patterns for both straight channel (Bocchiola et al, 2008) and curved reach (Schmocker and Weitbrecht, 2013), but could not provide any evidence to confirm the theory by Diehl (1997). De Cicco et al (2020 observed in a flume experiment that LW elements released at the flume centerline occupied a narrow area of the flume center for F r=0.50, whilst for lower F r (i.e.…”
Section: Introductionmentioning
confidence: 70%
“…However, in our experiments cylindrical artificial stems were used, under different approach flow conditions, so conclusions about the influence of irregular stem geometry cannot be drawn. Based on the work done in De Cicco et al (2016Cicco et al ( , 2020, where they investigated the effect of the pier shape in the accumulation of LW at bridges for river approach flows, it was concluded that the round nose piers are less prone to LW blockage when compared to other geometries. On the contrary, in Schalko et al (2020) they concluded that only a minor effect was observed for bridge pier shapes in terms of blocking probability.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The classification of LW includes stems longer than 1 m and with a diameter larger than 0.10 m (Braudrick et al., 1997; Ruiz‐Villanueva, Piégay, Gurnell, et al., 2016; Wohl et al., 2016). The transport of LW can induce dangerous obstructions at hydraulic infrastructures like bridges, weirs and spillways during floods (Allen et al., 2014; Bénet et al., 2021; De Cicco et al., 2016, 2020; Gschnitzer et al., 2017; Hartford et al., 2016; Hartlieb, 2012; Iroumé et al., 2015; Panici & de Almeida, 2018; Pfister, Capobianco, et al., 2013; Piton et al., 2020; Schalko et al., 2020; Schmocker & Hager, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors focused their attention on the mechanisms of instability of the emerging rigid vegetation when major flood events occur (Calvani et al., 2019; Francalanci et al., 2020; Miyamoto & Kimura, 2016; Tanaka & Yagisawa, 2009). Other authors investigated the dynamics of mobilization and transport of woody debris already present in the riverbed (Bocchiola at al., 2008; Persi et al., 2016, 2018, 2019; Ruiz‐Villanueva et al., 2016; Sibilla et al., 2020; Zischg et al., 2018), the risk and the probability of wood accumulation at bridge piers and deck (Diehl, 1997; Panici et al., 2020; Shalko et al., 2020a), the geometric parameters that contribute to worsen such an accumulation (De Cicco et al., 2015), their influences on the stability of the accumulations (De Cicco et al., 2020; Panici & de Almeida, 2018) and the engineering strategies to reduce the occurrence of such situations (Rossi & Armanini, 2019; Schalko et al., 2020b; Schmocker & Weitbrecht, 2013). The entrapment probability increases if the bridge has prominent abutments, low freeboard, and piers in the riverbed, but also in the absence of piers and in conditions of a supercritical flow if the bridge is already partially occluded, or in presence of a subcritical flow if the entrance is initially not dammed (see Gschnitzer et al., 2017).…”
Section: Introductionmentioning
confidence: 99%